No Evidence of Racial Differences in Endothelial Function and Exercise Blood Flow in Young, Healthy Males Following Acute Antioxidant Supplementation - Kappus, Rebecca M.; Bunsawat, Kanokwan; Rosenberg, Alexander J.; Fernhall, Bo (International Journal of Sports Medicine, 2017)
This study investigated the effects of acute antioxidant supplementation on endothelial function, exercise blood flow and oxidative stress biomarkers in 9 young African American compared to 10 Caucasian males (25.7±1.2 years). We hypothesized that African American males would have lower exercise blood flow and endothelial responsiveness compared to Caucasian males, and these responses would be improved following antioxidant supplementation. Ultrasonography was used to measure blood flow during handgrip exercise. Endothelial function was assessed using flow-mediated dilation, and lipid peroxidation was assessed by measuring levels of malondialdehyde-thiobarbituric acid reactive substances. African American males exhibited lower endothelial function than Caucasians at baseline (8.3±1.7 vs. 12.2±1.7%) and the difference was ameliorated with antioxidant supplementation (10.7±1.9% vs. 10.8±1.8%), but the interaction was not significant (p=0.10). There were no significant changes in malondialdehyde-thiobarbituric acid reactive substances following antioxidant supplementation. There was a significant increase in brachial blood flow and forearm vascular conductance with exercise but no differences with antioxidant supplementation. There were no group differences in exercise responses and no differences with antioxidant supplementation, suggesting a lack of influence of oxidative stress during exercise in this cohort.
Keywords: endothelial function; exercise blood flow; oxidative stress; antioxidant; racial differences; vascular